Effects of Isometric Hip Extension Using Thera-band on Hip Muscle Activities During Side-lying Hip Abduction Exercise in Participants With Gluteus Medius Weakness - Sae-hwa Kim; Hyun-ji Lee; Seok-hyun Kim; Seung-min Baik; Heon-seock Cynn (Korean Research Society of Physical Therapy, 2024)
Background: Weakness of gluteus medius (Gmed) is related with musculoskeletal disorders. Individuals who experience weakness in the Gmed may activate the tensor fasciae latae (TFL) as a compensatory mechanism. Application of isometric hip extension (IHE) with Thera-band may affect the activities of the Gmed, gluteus maximus (Gmax), and TFL, and the activity ratio of Gmed/TFL during side-lying hip abduction (SHA). Objects: To determine the influences of IHE during SHA on Gmed, Gmax, and TFL activities in participants with Gmed weakness. Methods: Three types of SHA exercises were performed: 1) traditional SHA in the frontal plane (SHA-T), 2) SHA with IHE applying Thera-band in the frontal plane (SHA-IHE), 3) and SHA with isometric hip flexion (IHF) applying Thera-band in the frontal plane (SHA-IHF). Results: SHA-IHE significantly showed higher Gmed and Gmax activities than SHA-T and SHA-IHF. SHA-IHF significantly showed higher activity of TFL than SHA-T or SHA-IHE. The ac-tivity ratio of Gmed/TFL was significantly higher in the SHA-IHE, SHA-T, and SHA-IHF, in that order. Conclusion: The SHA-IHE resulted in higher activities of Gmed, Gmax and a higher muscle ratio of Gmed/TFL.